Penerapan Manajemen Pelayanan Prima untuk Peningkatan Kepuasan Calon Jamaah Haji dan Umrah di PT Mabruro Sidoarjo - Almun Wakhida Candra; Renny Oktafia (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to determine the application of excellent service management to increase the satisfaction of prospective pilgrims at PT Mabruro Sidoarjo. The method used in this research is qualitative method. The data collection techniques used in this research were observation, interview and documentation. The result of this research is PT Mabruro Sidoarjo gives satisfaction to prospective piligrims by providing excellent service from registration to completion of hajj activities with trust and sincerity.